2000
DOI: 10.1103/physrevb.63.020507
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics and ordering of a cuprate stripe antiferromagnet

Abstract: In La 1.48 Nd 0.4 Sr 0.12 CuO 4 the 139 La and 63 Cu nuclear quadrupole resonance relaxation rates and signal wipeout upon lowering temperature are shown to be due to purely magnetic fluctuations. They follow the same renormalized classical behavior as seen in neutron data, when the electronic spins order in stripes, with a small spread in spin stiffness ͑15% spread in activation energy͒. The La signal, which reappears at low temperatures, is magnetically broadened and experiences additional wipe out due to sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
37
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 26 publications
6
37
0
Order By: Relevance
“…The work by Imai's group suggesting that local stripe order in variants of La 2−x Sr x CuO 4 could be detected through the "wipeout effect" of Cu NQR has motivated a considerable number of further studies using Cu and La NMR and NQR (Curro et al, 2000a;Hunt et al, 2001;Julien et al, 1999Julien et al, , 2001Simovič et al, 2002;Singer et al, 1999;Suh et al, 1999Suh et al, , 2000Teitel'baum et al, 2001Teitel'baum et al, , 2000. Although there has been some controversy over details of the interpretation (and in certain cases, there may be differences between samples), it is now generally agreed that NQR and NMR are sensitive to the onset of slow spin fluctuations whose appearance tends to correlate with the onset of local charge stripe pinning as determined by diffraction.…”
Section: E Other Probesmentioning
confidence: 99%
“…The work by Imai's group suggesting that local stripe order in variants of La 2−x Sr x CuO 4 could be detected through the "wipeout effect" of Cu NQR has motivated a considerable number of further studies using Cu and La NMR and NQR (Curro et al, 2000a;Hunt et al, 2001;Julien et al, 1999Julien et al, , 2001Simovič et al, 2002;Singer et al, 1999;Suh et al, 1999Suh et al, , 2000Teitel'baum et al, 2001Teitel'baum et al, , 2000. Although there has been some controversy over details of the interpretation (and in certain cases, there may be differences between samples), it is now generally agreed that NQR and NMR are sensitive to the onset of slow spin fluctuations whose appearance tends to correlate with the onset of local charge stripe pinning as determined by diffraction.…”
Section: E Other Probesmentioning
confidence: 99%
“…Structurally, this material is almost identical to the prototypical high temperature superconductor La 2−x Sr x CuO 4 , but undergoes a subtle phase transition to the low temperature tetragonal (LTT) structure below T LT = 135K [12]. Instead of superconducting below T c ∼ 35K, this system exhibits glassy magnetic order below T N ∼ 25K [12,13,14,15,16,17,18], and elastic NS measurements have identified static long-range spin and structural modulations that are likely produced by stripe order [5]. The slow spin fluctuations in this system dominate the NMR response of the La and Cu nuclei [14,16,19].…”
mentioning
confidence: 99%
“…Furthermore, 17 O (I=5/2) has a quadrupolar moment ( 17 Q = -2.56 ×10 −26 cm 2 ), so it is sensitive to the EFG at the nuclear site, which is a measure of the local hole doping [21]. Although previous NMR studies have shown the presence of spatial modulations due to doping inhomogeneities in superconducting La 2−x Sr x CuO 4 [6,8] 17 O by annealing in 17 O 2 gas at 600 • C for 24 hours. The powder samples were then mixed with epoxy and aligned along the c-axis by curing in an external field.…”
mentioning
confidence: 99%
See 2 more Smart Citations